SWOT-based teacher quality improvement strategy at MA Inovatif Daarul Ihsan Cimahi - Arini Nur Fariha; Nugraha Suharto; Asep Dikdik (Inovasi Kurikulum, 2025)
Improving the quality of educators and education personnel is a crucial element in building a superior education system. MA Inovatif Daarul Ihsan Cimahi is committed to improving teaching standards for a better learning environment. This study aims to determine strategies to optimize the quality of educators and education personnel by combining quantitative and qualitative case study methodologies. Data was collected through a Google Forms-based questionnaire and a SWOT analysis was conducted to evaluate the institution's condition. The analysis results show that the strengths are competent teaching staff and innovative learning methods, while the weaknesses are inconsistencies in teacher certification and lack of administrative support. Opportunities for improvement lie in policy synchronization and supervision, while threats include limited parental support. Strategic recommendations include improving school management, developing teacher competencies, expanding collaboration networks and creating a more personalized curriculum. The main priority is to improve school management to make the next strategy more effective, which is expected to improve the quality of education personnel and produce quality and competitive graduates.   Abstrak Peningkatan kualitas pendidik dan tenaga kependidikan merupakan unsur krusial dalam membangun sistem pendidikan yang unggul. MA Inovatif Daarul Ihsan Cimahi berkomitmen meningkatkan standar pengajaran untuk menciptakan lingkungan belajar yang lebih baik. Penelitian ini bertujuan untuk mengetahui strategi yang dapat mengoptimalkan kualitas pendidik dan tenaga kependidikan pada dengan menggunakan pendekatan yang memadukan metodologi kuantitatif dan kualitatif studi kasus. Pengumpulan data dilakukan melalui kuesioner berbasis Google Form dan dilakukan analisis SWOT untuk mengevaluasi kondisi institusi. Hasil analisis menunjukkan kelebihan berupa tenaga pengajar yang kompeten dan metode pembelajaran yang inovatif, sedangkan kelemahannya berupa inkonsistensi sertifikasi guru dan kurangnya dukungan administratif. Peluang perbaikan terletak pada sinkronisasi kebijakan dan pengawasan, sedangkan ancamannya berupa terbatasnya dukungan orang tua. Rekomendasi strategisnya antara lain perbaikan manajemen sekolah, pengembangan kompetensi guru, perluasan jaringan kolaborasi, dan pembuatan kurikulum yang lebih personal. Prioritas utamanya adalah perbaikan manajemen sekolah agar strategi selanjutnya lebih efektif sehingga diharapkan dapat meningkatkan kualitas pendidik tenaga kependidikan, dan menghasilkan lulusan yang berkualitas dan berdaya saing. Kata Kunci: analisis SWOT; kualitas pendidik; kualitas pendidikan